2021
DOI: 10.1021/acs.joc.1c00985
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cardiotonic Steroids Oleandrigenin and Rhodexin B

Abstract: This article describes a concise synthesis of cardiotonic steroids oleandrigenin (7) and its subsequent elaboration into the natural product rhodexin B (2) from the readily available intermediate ( 8) that could be derived from the commercially available steroids testosterone or DHEA via 3 step sequences. These studies feature an expedient installation of the β16-oxidation based on β14-hydroxyl directed epoxidation and subsequent epoxide rearrangement. The following singlet oxygen oxidation of the C17 furan mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Likewise, the sulfated glycopeptidolipids comprising α ‐linked ʟ‐rhamnose ( α ‐ʟ‐Rha) moieties have been isolated from the bacterial pathogen of M. fortuitum [8c] . Besides pathogenic biomolecules, specific α ‐rhamnoside linkages are often present in synthetic as well natural bioactive structures, [9] including bis‐steroidal pyrazine (anticancer), [9a] cardiotonic steroid rhodexin B, [9b–d] sitosterol glycoside, [9e,f] and cytotoxic agent calicheamicin (antitumor antibiotic) [9g–i] . In addition, α ‐ʟ‐Rha glycosyl component serves as key chiral‐intermediate in developing clinical agents of profound relevance such as afzelin; antiviral drug against SARS coronavirus, [10a,b] SL0101 analogues having specific protein kinase (RSK) inhibitor activity, [10c] and a potent natural flavonoid quercitrin of numerous pharmaceutical activities [10d–f] …”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the sulfated glycopeptidolipids comprising α ‐linked ʟ‐rhamnose ( α ‐ʟ‐Rha) moieties have been isolated from the bacterial pathogen of M. fortuitum [8c] . Besides pathogenic biomolecules, specific α ‐rhamnoside linkages are often present in synthetic as well natural bioactive structures, [9] including bis‐steroidal pyrazine (anticancer), [9a] cardiotonic steroid rhodexin B, [9b–d] sitosterol glycoside, [9e,f] and cytotoxic agent calicheamicin (antitumor antibiotic) [9g–i] . In addition, α ‐ʟ‐Rha glycosyl component serves as key chiral‐intermediate in developing clinical agents of profound relevance such as afzelin; antiviral drug against SARS coronavirus, [10a,b] SL0101 analogues having specific protein kinase (RSK) inhibitor activity, [10c] and a potent natural flavonoid quercitrin of numerous pharmaceutical activities [10d–f] …”
Section: Introductionmentioning
confidence: 99%
“…The Nagorny group has long-standing interests in streamlining the medicinal chemistry exploration of cardiotonic steroids by developing new strategies for the aglycone synthesis and their selective glycosylation. Previously, we described strategies for the installation of native (α)- l -rhamnoside moiety at the C3-position of various cardiotonic steroids. It was observed that cardiotonic steroids such as 5 containing C3 and C19 oxidation undergo competitive C19 glycosylation that produces a complex mixture of products such as 7 and 8 ( cf . Figure B) .…”
mentioning
confidence: 99%
“…Our group has long-standing interests in developing and exploring new methods for the selective synthesis and glycosylation of natural products . Recently, we achieved a concise 15 step synthesis of C16-oxidized aglycone oleandrigenin that is present in a variety of cardiotonic steroids including natural cardenolide oleandrin (Figure B) . Oleandrin is the primary ingredient in the extracts of the Mediterranean plant Nerium oleander that is responsible for the medicinal properties of this shrub .…”
mentioning
confidence: 99%
“…Our prior work focusing on glycosylation of 10 with rhamnose-based donors uncovered significant sensitivity of 10 to Lewis acids and bases . Consequently, acid labile protection on a trichloroacetimidate rhamnose donor was used to generate natural cardenolide rhodexin B.…”
mentioning
confidence: 99%